The Falconer - May, Elizabeth (May, Elizabeth [<<The>> Falconer trilogy], 2014)
In 1844 Edinburgh eighteen-year-old Lady Aileana Kameron is neither an ordinary debutante, nor a murderess...she is a Falconer, a female warrior born with the gift for hunting and killing the faeries who prey on mankind and who killed her mother